Analisis Reaksi Customer Loyal Scarlett Whitening pada Misleading Advertising Paris Fashion Show 2022 - Berliana Bunga Priscagita; Devi Purnamasari (STARKI, 2023)
Scarlett Whitening is one of the brands with the highest rating in the Shopee and Tokopedia Market Place with a market share of 18.9%. At the end of February 2022, Instagram was shocked by the news that 10 Indonesian brands, one of which was Scarlett Whitening, had managed to go international and take part in the Paris Fashion Week 2022 event. In fact, this event was misleading information received by the public that these 10 brands were actually attending the Paris Fashion event. GEKRAFS (National Creative Economy Movement) Show. The date for the Paris Fashion Week 2022 event with the Paris Fashion Show 2022 is used by the brand as a marketing strategy. This study used a qualitative method with a case study approach. The theory used in this research is misleading advertising, ambush marketing, customer loyalty, and digital customer experience. The results of this study indicate that loyal customers of Scarlett Whitening do not care about negative news due to misleading advertising about the brand in implementing their marketing strategy because Scarlett Whitening customers are concerned with the quality of products that are considered suitable for themselves and their personal experiences with products from that brand. Abstrak Scarlett Whitening menjadi salah satu brand dengan rating tertinggi dalam Market Place Shopee dan Tokopedia dengan pangsa pasar sebesar 18,9%. Pada akhir bulan Februari 2022 Instagram dihebohkan oleh pemberitaan 10 brand Indonesia salah satunya adalah Scarlett Whitening berhasil go international dan turut dalam event Paris Fashion Week 2022. Faktanya, peristiwa ini merupakan sebuah misleading informasi yang diterima oleh masyarakat bahwa sebenarnya 10 brand tersebut mengikuti acara Paris Fashion Show GEKRAFS (Gerakan Ekonomi Kreatif Nasional). Tanggal pelaksanaan event Paris Fashion Week 2022 dengan Paris Fashion Show 2022 dimanfaatkan oleh brand tersebut sebagai strategi marketing. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus (case study). Teori yang digunakan dalam penelitian ini adalah misleading advertising, ambush marketing, loyalitas pelanggan, dan digital customer experience. Hasil penelitian ini menunjukan bahwa customer loyal dari Scarlett Whitening tidak memperdulikan adanya pemberitaan negatif akibat dari misleading advertising tentang brand tersebut dalam penerapan strategi marketingnya karena pelanggan Scarlett Whitening mementingkan kualitas produk yang dianggap cocok dengan dirinya dan pengalaman pribadinya bersama produk dari brand tersebut.